Solar Rich and Water Poor: The Case for Solar Desalination in El Paso, Texas. Issue 1 (2nd January 2020) - Delgado, William; Beach, Timothy; Luzzadder-Beach, Sheryl
Abstract : Desalination is an increasingly important water source for the sunny, arid city of El Paso, Texas. As the city's population grows, El Paso Water, the city's water utility, has had to drill deeper into the Hueco Bolson aquifer, a primary water source for El Paso. This deeper drilling into the Hueco Bolson, however, has yielded progressively more saline water. In response, El Paso Water and administrators from Fort Bliss jointly constructed a reverse osmosis desalination plant to protect the Hueco Bolson's freshwater supplies and expand the city's water sources. Reverse osmosis water desalination, however, is an expensive, energy-intensive process currently dependent on carbon-heavy fossil fuels. Solar energy, however, is an abundant, carbon-free energy source that could potentially reduce the energy costs and carbon footprint of the reverse osmosis desalination process. We hypothesize that building a solar microgrid that supplies El Paso's desalination plant with energy in tandem with the regional grid will reduce the plant's energy expenditures in the long term compared to solely buying energy from the regional grid. We used the Hybrid Optimization for Multiple Energy Resources (HOMER) model created by the National Renewable Energy Laboratory. The results suggest that a solar microgrid whose modules use one axis tracker could reduce the plant's energy expenses. Key Words: desalination, solar energy, water resources.